Perbandingan Metode Analisis Kadar Senyawa dan Toksisitas Merkuri (Hg) dalam Sampel Biologis - Priscinya Christiana Debora; Sofianti Hidayat; Mochamad Galuh Ryandha; Marsah Rahmawati Utami; Lina Nurfadhila (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Mercury or mercury (Hg) is a type of metal as an organic and inorganic compound that can be found in nature and is spread in rocks, ores, soil, water and air. Mercury in the body can be detected in biological materials such as urine, blood, breast milk and hair. This study aims to analyze the content and toxicity of mercury (Hg) in biological samples such as blood, hair, urine and breast milk with various analytical methods including CV-AAS, AAS, CV-AFS, ICP-MS, FI-CV-AAS, and Mercury Analyzers. Data collection was based on the Literature Review by collecting several published research journals both at national and international levels which were filtered according to inclusion and exclusion criteria using the PRISMA method (Preferred Reporting Item for Systematic Review and Meta-Analysis). The method used depends on the needs of the analysis, its sensitivity and availability. Of the several methods used, AAS or atomic absorption spectrophotometry is the most commonly used method, because this method is simple and considered fast for analyzing mercury levels in biological samples.